2021
DOI: 10.3390/pathogens10081023
|View full text |Cite
|
Sign up to set email alerts
|

High Mortality and Graft Loss after Infective Endocarditis in Kidney Transplant Recipients: A Case-Controlled Study from Two Centers

Abstract: Kidney transplant recipients (KTRs) tend to develop infections with characteristic epidemiology, presentation, and outcome. While infective endocarditis (IE) is among such complications in KTRs, the literature is scarce. We describe the presentation, epidemiology, and factors associated with IE in KTRs. We performed a retrospective case/control study which included patients from two centers. First episodes of definite or possible IE (Duke criteria) in adult KTRs from January 2010 to December 2018 were included… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In the French case–control study comparing patients with infective endocarditis and SOT amongst patients with SOT but no infective endocarditis, the former had a survival rate at 1 and 5 years after the index event of 58 and 50% as compared with survival rates of 100 and 85% amongst the latter, respectively. Death-censored graft survival was similarly lower in cases than controls at 1 year (81 vs. 100 months) and 5 years (29 vs. 87 months) [8 ▪ ]. Similarly, Eichenberger et al have reported outcomes of increased mortality, increased need for extracorporeal membrane oxygenation, and/or mechanical ventilation, and greater number of thromboembolic events when infective endocarditis occurs during the index hospitalization for transplantation as compared with patients undergoing transplantation with no infective endocarditis [12 ▪▪ ].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In the French case–control study comparing patients with infective endocarditis and SOT amongst patients with SOT but no infective endocarditis, the former had a survival rate at 1 and 5 years after the index event of 58 and 50% as compared with survival rates of 100 and 85% amongst the latter, respectively. Death-censored graft survival was similarly lower in cases than controls at 1 year (81 vs. 100 months) and 5 years (29 vs. 87 months) [8 ▪ ]. Similarly, Eichenberger et al have reported outcomes of increased mortality, increased need for extracorporeal membrane oxygenation, and/or mechanical ventilation, and greater number of thromboembolic events when infective endocarditis occurs during the index hospitalization for transplantation as compared with patients undergoing transplantation with no infective endocarditis [12 ▪▪ ].…”
Section: Discussionmentioning
confidence: 93%
“…to be an equally common or even more common agent of infective endocarditis than S. aureus [15 ▪ ,16,19]. Tamzali et al [8 ▪ ] in their case–control study, also found enterococci as the most common cause of infective endocarditis in renal transplant recipients. In contrast, a registry-based study conducted in France and Spain exclusively amongst infective endocarditis in heart transplant recipients showed that Staphylococcus spp.…”
Section: Etiologymentioning
confidence: 93%
See 3 more Smart Citations